Quality Testing of Frozen Loin Tuna (Thunnus albacares) - Dewi, Jelita; Sayuti, Mohammad; Salampessy, Randi B.S (Program Studi Budidaya Perairan Universitas Mataram, 2024)
Indonesia as the largest tuna producing country has potential in the international tuna market. Frozen tuna loin is a fishery product made from fresh tuna as raw material. This study aims to determine the quality of frozen tuna loin products at PT. Treasures of the Ambon Maluku Ocean. Organoleptic quality testing refers to SNI 01-4110.1-2006, ALT test refers to SNI 2332.3: 2015, E. coli refers to SNI 2332.1: 2015., Salmonella refers to SNI 01-2332-2006), chemistry (histamine) refers to SNI 2354.10: 2009 , direct observation of the application of cold chain in the processing room and frozen tuna loin products, yield calculations were carried out 10 times. Observations for productivity calculations were carried out 10 times. Organoleptic test results for raw materials scored 8 while organoleptic frozen tuna loin products scored 8. Microbiological test results for tuna loin products ALT 1.7 X 10Â³ col/g, E. coli <3 APM/g, Salmonella negative. The result of trimming yield test (trimming l) was 96.53%, and trimming II was 90.26%, while the result of trimming productivity test (trimming l) was 104.42 kg/hour/person and trimming II) 152.21 kg/hour/person. Overall frozen tuna loin products comply with SNI standards for frozen tuna loin (7968: 2014).